Who Emigrates From a Wealthy, Peaceful Country? And Who Comes Back? Evidence From Norway - Tønnessen, Marianne; Constant, Amelie F.; Syse, Astri (Population space and place, 2025)
ABSTRACT Each year, millions of people emigrate from wealthy, peaceful countries. In this paper, we summarise research and available international data on the numbers and characteristics of those who move from wealthy countries in general. Next, we utilise rich Norwegian individual‐level register data and various quantitative methods to provide a broad description of emigrants from Norway over recent decades, as well as migration back to Norway, with a focus on heterogeneities among the emigrants. Finally, we summarise in seven key points how our descriptive findings can inform the research literature and relevant policy fields. For instance, our results reveal that emigration from Norway has become considerably less frequent for most immigrant groups in Norway, challenging notions that people are increasingly on the move between countries.